Casting a Wide Multidisciplinary Net: Two-Year Colleges as Human Services Contributors in Their Communities - Alan M. Schwitzer; Pat Huber; Nic Schmoyer (Journal of Human Services)
The need among human services professionals for interdisciplinary approaches to meeting population needs, especially in the current COVID-19 and Black Lives Matters (BLM) contexts, is unprecedented. This conceptual article reviews the current research and practice literature in order to discuss two-year colleges as often-overlooked partners in meeting community needs. We present the argument that American two-year colleges, by design, can be human services partners when addressing the inequities, economic and other deficiencies, and marginalization based on racial and ethnic discrimination or similar dynamics found in our communities. Specifically, we demonstrate the relationships between human services, on one hand, and the work of community colleges in their roles as economic engines intended to generate socio-economic security, as academic success centers intended to mitigate obstacles to learning outcomes, as mechanisms for social justice intended to produce life improvements among marginalized populations, and as mental health and wellness supports intended to reduce barriers to achievement. We rely on our own experiences in the Virginia Community College System (VCCS) as illustrations, and we use the work of one sample institution to provide a start-to-finish example of the overlap between human services goals and community colleges.